2016
DOI: 10.1002/clen.201500368
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Design Methodological Approach for Enhanced Cadmium Ions Bioremoval by Opuntia Biomass

Abstract: The bioremoval efficiency of Opuntia biomass, a low-cost biosorbent and renewable resource, for cadmium ions from aqueous solutions was investigated using factorial design methodology. The functional groups involved in the sorption process were identified by FTIR spectroscopy. A factorial experimental design technique, the full factorial design 3 3 , has been used for enhanced cadmium ions bioremoval. Three factors were considered: protonation of the sorbent, initial cadmium concentration, and sorbent dosage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Zhang et al [10] investigated cadmium adsorption using magnetic alginate beads linked to Rhizopus sp., determined that under optimal conditions the removal of Cd was 89% and that the addition of Pb could reduce the rate of removal of Cd under the same conditions. Similar studies were carried out by Abdelwahab et al [11] with modified and unmodified guava leaves in the adsorption of cadmium ions from aqueous solutions, reporting the rapid removal of these ions, following a pseudo-second order model; Rosique et al [12], reported similar results in the removal of Cd with Opuntia; Iqbal and Khera [13] studied the removal of Pb and Cu in aqueous solution using Fumaria indica, adapting the Freundlich isothermal model to the adsorption data for both metals. De Moraes-Ferreira et al [14], used two biosorbents obtained from the aquatic plants Salviniasp.…”
Section: Introductionsupporting
confidence: 58%
“…Zhang et al [10] investigated cadmium adsorption using magnetic alginate beads linked to Rhizopus sp., determined that under optimal conditions the removal of Cd was 89% and that the addition of Pb could reduce the rate of removal of Cd under the same conditions. Similar studies were carried out by Abdelwahab et al [11] with modified and unmodified guava leaves in the adsorption of cadmium ions from aqueous solutions, reporting the rapid removal of these ions, following a pseudo-second order model; Rosique et al [12], reported similar results in the removal of Cd with Opuntia; Iqbal and Khera [13] studied the removal of Pb and Cu in aqueous solution using Fumaria indica, adapting the Freundlich isothermal model to the adsorption data for both metals. De Moraes-Ferreira et al [14], used two biosorbents obtained from the aquatic plants Salviniasp.…”
Section: Introductionsupporting
confidence: 58%
“…Hence, the surface of AO-PAN-g-CS/Fe 3 O 4 was positively charged. [22] So the q e was low at low pH. However, the H + concentration decreases with the increase of solution pH.…”
Section: Effect Of Ph On Heavy Metal Ions Adsorptionmentioning
confidence: 95%
“…In the region of 1030-1000 cm −1 , a broad band, an indication of C−O and C=C vibrational stretching, was revealed. These are, in fact, typical FTIR spectra, corresponding to nonmodified plant biomass samples, where the lignocellulosic constituents are particularly outstanding [32,[47][48][49]. .…”
Section: Characterization Of Biomass Samplesmentioning
confidence: 97%
“…Raw lignocellulosic biomass was also used as a low-cost biosorbent, but the achieved efficiency was not as high as that with previous sorbents [29,30]. Despite this, biosorption has lately been presented as a very interesting technology, in line with the concept of the circular economy [31,32]. Efficient biowaste management is among the most important challenges in agrifood industries.…”
Section: Introductionmentioning
confidence: 99%